18F-FDGPET/CT improves diagnostic certainty over the modified Duke Criteria in blood culture negative infective endocarditis. (20th July 2021) - Primus, C; Bvekerwa, I; Clay, TA; Mccue, M; Wong, K; Uppal, R; Ambekar, S; Das, S; Bhattacharyya, S; Davies, LC; Woldman, S; Menezes, L
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Diagnosis of blood culture negative infective endocarditis (BCNIE) is challenging, with positive microbiology key in the modified Duke Criteria (mDC). ESC IE Guidelines (2015) recommend the use of 18F-FDG PET/CT (PET) in cases where transoesophageal echocardiography (TOE) is equivocal and where cardiac implantable device-related IE (CIDRE) is suspected. We explored the role of PET to improve diagnostic certainty in the challenging cohort of BCNIE. Methods: Retrospective review of all suspected BCNIE patients undergoing PET (10/2015 to 01/2021). Myocardial suppression technique was used in all cases, and studies were assessed for valve/device avidity. Patients were classified as definite/possible/rejected IE by mDC pre- and post-PET, with incremental benefit assessed by net reclassification index (NRI) versus actual diagnosis. Actual diagnosis was defined by Endocarditis Team consensus or surgical specimen (where available) at a minimum of 2-months following index admission. Results: PET was performed in 110/807 (13.6%) cases overall. BCNIE prevalence was 18% across the total cohort, with 25/110 (22.7%) PET studies in BCNIE patients (male = 17, mean age 65). (p = 0.16 for PET in BCNIE compared to overall). PET was undertaken in 8 CIDRE, 9 native IE (NVE) and 10 prosthetic IE (PVE); 2-patients had suspected CIDRE + PVE. TOE was performed in all cases, and surgery was required in 8/25 patients. IE was confirmed in 44% of cases. PET sensitivity, specificity, positive and negative predictive values were 73%, 93%, 89% and 81%, respectively. Addition of PET to the mDC improved re-classification to definite or rejected IE, with NRI 0.633 (positive NRI 0.3; negative 0.333), and added weight to the original mDC classification in 14/25 (56%) of cases. Conclusion: PET improves diagnostic certainty when combined with mDC in the evaluation of patients with BCNIE across NVE, PVE and CIDRE.